Financial leverage and profitability of listed construction companies in Malaysia/ Siti Najihah Bakar - Bakar, Siti Najihah (2017)
This study aims to examine the financial leverage and profitability of listed construction companies in Malaysia by finding the relationship between debt ratio (DR), debt equity ratio (DER), interest coverage ratio (ICR) and long term debt ratio (LTDR). The data are collected from 2008 - 2015 and analysis using Pooled Ordinary Least Square (POLS). The final result indicated that debt ratio (DR) and debt equity ratio (DER) has negative relationship with dependent variable return on asset (ROA). Therefore interest coverage (ICR) and long term debt ratio (LTDR) has a positive relationship to return on asset (ROA).Therefore, decision of financial leverage is important because it will give an impact towards the firm profitability.